Teknik Permainan Appogiatura Piano Pada Lagu “Waltz In A Minor, B.150, Op.Posth” Karya Frederic Chopin - Yoseph Fransiscus Sihombing; Testi Zebua; Aprinaldi Simorangkir; Monang Asi Sianturi; Rowilson Nadeak (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2023)
This research aims to determine the techniques for playing appogiatura piano in the song "Waltz in a minor, B.150, Op.Posth" by Frederic Chopin. The author uses descriptive qualitative methods. The object of this research is the score for Waltz in a minor, B.150, Op.Posth" by Frederic Chopin. The data analysis techniques used are data reduction, data presentation, and data conclusions. The results and discussion of this research are Frederic Chopin's "Waltz in a minor, B.150, Op. Posth" which is a solo performance that uses playing techniques such as Appoggiatura and is equipped with techniques such as mordent, trill, triplet-quintuplet, and legato, as well as dynamics so that what is produced in part A1, wants to describe a sad atmosphere because of the legato technique which makes it lilting, then in part B with appoggiatura and legato techniques wants to describe a cheerful atmosphere as if there is hope, supported by a Major chord at the beginning, variations melodies, and lots of appoggiatura, triplet-quintuplet ornaments as sweeteners. Next, section A' again depicts a sad atmosphere, but the modulation to A Major makes hope even more visible. But in section A2, the sweet dance atmosphere, the hopes built in sections B and A' return to an atmosphere of sadness which then in the Coda section ends with an ornamental trill at the end of the song so that it can depict an atmosphere of decline.